Preparation, in vitro and in vivo Characteristics of Floating in situ Gel of Carvedilol Using Semi Synthetic and Natural Polymers to Enhance the Oral Bioavailability - Ramalingam, Ananthakumar; Sukumaran, Sathesh Kumar; Krishnan, Chitra (Indian Journal of Pharmaceutical Education and Research, 2024)
Background/Aim: The purpose of this study was to design and prepare floating in situ gel to sustain Carvedilol (CVD) release and enhance oral bioavailability. Various floating in situ gel formulations of the CVD were prepared by ionic gelation method. Materials and Methods: A systematic approach in the design of the formulations was adopted, were using Hydroxypropyl Methyl Cellulose (HPMC K4M), Hydroxypropyl Methyl Cellulose (HPMC 100LV), Sodium alginate, Mimosa pudica seed mucilage and Limonia acidissima gum in various concentrations along with gas generating agent (sodium bicarbonate) were investigated for its physicochemical properties (in vitro floating behavior, drug release profile, etc.). Subsequently, a final optimization step is involved based on the physicochemical properties to achieve the desired effect. Results: Based on the study, the formulation with HPMC K4M, HPMC 100LV, Sodium alginate, and Mimosa pudica seed mucilage (F17) showed good floating properties (60 sec floating lag time) with drug release of 96.98 ± 2.1% for 12 hr and the drug release mechanism was found to be zero order (R2 = 0.894). In vivo X-ray studies of F17 in albino rabbits showed a good floating ability up to 8 hr. Bioavailability of optimized and control (CARLOC) was found to be 41.95 ± 0.8892 μg.hr/ mL and 26.36 ± 1.1603 μg.hr/mL respectively. The accelerated stability study was performed with optimized formulation and it was observed stable during the study. Conclusion: It was concluded that the floating in situ gel of Carvedilol developed with natural polymer is suitable for GRDDS to enhance oral bioavailability.
Keywords: GRDDS; Mimosa pudica seed mucilage; Limonia acidissima gum; In situ gel; Carvedilol; HPMC K4M